A new species of Saurida (Pisces: Synodontidae) from the Mascarene Plateau, Western Indian Ocean - Russell, Barry C. (Zootaxa, 2015)
A new species of lizardfish, Saurida tweddlei n.sp., from the Mascarene Plateau, Western Indian Ocean, is described and figured. The new species is characterised by the following combination of characters: dorsal fin with 12–13 rays; pectorals with 14–15 rays; lateral-line scales 53–55; transverse scale rows above lateral line 4½, below lateral line 5½; pectoral fins moderately long (extending to or just beyond a line from origin of pelvic fins to origin of dorsal fin); 2 rows of teeth on outer palatines; 0–3 teeth on vomer; tongue with about 4–5 rows of teeth posteriorly; caudal peduncle compressed (depth greater than width); stomach and intestine pale whitish. A key to the species of Saurida of the Western Indian Ocean is provided.